Investor's Behavior in Makassar Against Portfolio Investment Risk the Stock - Rosnani Said (Research Synergy Foundation, 2019)
The objective of this research is to know investor behavior toward investment risk in a stock portfolio by using demography approach. The type of this research is field research by using questionnaires to stock investors registered at a security company in the Makassar area. The result is investors' behavior in Makassar against investment risk is neutral to the risk of stocks being a portfolio.